Sustainable Competitive Advantage Through Strategic Agility at the Radio of Suara Surabaya - Eva Desembrianita; F. Risallah (IECON: International Economics and Business Conference, 2025)
The purpose of this study is to identify the implementation of strategic agility that contributes to Sustainable Competitive Advantage at the radio of Suara Surabaya (SS). The phenomenon of SS's competitive advantage is manifested as a leading radio media in Surabaya and far beyond East Java. SS radio's reliability has been lasting for more than 42 years of broadcasting until now. The study discovered a uniqueness of applying strategic agility by the SS radio in responding and acting quickly to anticipate business obstacles faced. A qualitative descriptive analysis approach is used to obtain an overview of the implementation of strategic agility at SS Radio. The implementation carried out by the management results in business innovation and differentiation as a strategic model used in maintaining its competitiveness. This study collects the data by employing interviews, observations and documentation of three sampling subjects namely Human Resource managers, senior broadcasters and radio audiences. Source triangulation and technique triangulation were applied to ensure the validity of the data. The study found that SS radio demonstrates strategic agility through innovations focused on upgrading technological devices on broadcasting so that the radio is capable of synergizing on and off air platforms such as facebook, twitter, website, instagram and radio streaming. The radio also increases audience involvement in supporting broadcast programs, through the so-called citizen journalism model. As a result, SS Radio has been admittedly able to overcome business obstacles with agility in its business strategies. The radio has proved to have a wide market share reaching 25.000 dial callers per month and 21.000 internet audiences in 25 countries. It shows that the SS radio will always sustain this competitive advantage.